Scanning electron microscopy of Salmonella biofilms on various food-contact surfaces in catfish mucus. (September 2018) - Dhowlaghar, Nitin; Bansal, Mohit; Schilling, Mark W.; Nannapaneni, Ramakrishna
Abstract: The objective of this study was to determine the growth and survival of Salmonella enterica in the presence of high and low concentrations (375 μg/ml and 15 μg/ml) of catfish mucus extract at 10 °C and 22 °C for 63 days. The second objective of this study was to investigate the biofilm formation of Salmonella enterica serovar Blockley (7175) in catfish mucus extract for 48 h at 22 °C on four food-contact surfaces and to observe the biofilm populations using Scanning Electron Microscopy (SEM). The surface properties, surface roughness and surface energies were determined using contact angle measurement and atomic force microscopy. In 375 μg/ml of catfish mucus extract that was inoculated with 3 log CFU/ml, the growth of Salmonella counts were increased to a maximum of 6–7 log CFU/ml at 10 °C and 7–8 log CFU/ml at 22 °C in 7–14 d and decreased by 1–2 log CFU/ml from these peak levels at both 10 °C and 22 °C from 21 to 63 d. In 15 μg/ml of catfish mucus extract, Salmonella counts were in the range of 4–5 log CFU/ml at 10 °C and 5–6 log CFU/ml at 22 °C over 7–63 d of storage. By contrast, Salmonella counts were non-detectable in the absence of catfish mucus by 21–28 d of storage at 10 °C or 22 °C. The biofilm counts of S. Blockley (7175) on a stainless steel surface were 4 log CFU/cm 2 and 5.5 log CFU/cm 2 in 15 μg/ml and 375 μg/ml of catfish mucus extract respectively after 48 h incubation at 22 °C. SEM revelead that biofilm formation by S. Blockley (7175) was less in 15 μg/ml than 375 μg/ml of catfish mucus extract on stainless steel. In addition, SEM indicated that the visible biofilms were least on buna-N rubber as compared to stainless steel, polyethylene and polyurethane surfaces. Contact angle and atomic force microscopy confirmed that buna-N rubber was highly hydrophobic with low surface energy and low roughness when compared to other three surfaces. These findings indicate that Salmonella can utilize catfish mucus as a nutrient source to survive for longer periods and promote biofilm formation for its persistence on different food-contact surfaces. Highlights: Salmonella grew and survived in the presence of catfish mucus for up to 7 weeks tested. SEM showed decreased biofilm levels on stainless steel with decreasing concentration of catfish mucus. SEM showed least biofilm levels on buna-N rubber as compared to other food-contract surfaces. The lower biofilm levels on buna-N rubber was attributed due to its hydrophobic properties.